Pengaruh Kualitas Produk Terhadap Kepuasan dan Loyalitas Pelanggan TELKOM FLEXI - Wedarini, Ni Made Sinta (E-Jurnal Manajemen; Vol 2 No 5 (2013), 2013)
This study aimed to investigate the effect of product quality on customer satisfaction and loyalty TelkomFlexi. Data were collected from 120 customers Telkomflexi using purposive sampling method, and the data processed using the AMOS software analysis techniques Structural Equation Modelling (SEM). Research reveals there is a positive and significant correlation between the quality of the product to the customer satisfaction and loyalty Telkomflexi. Telkomflexi customer satisfaction has positive and significant impact on customer loyalty. Keywords : Product Quality, Customer Satisfaction, Customer Loyalty